Factores relacionados al conocimiento sobre medidas de bioseguridad frente al COVID 19 en personal de establecimientos de Salud I.4 San Juan y Bellavista Nanay - Pérez Cahuaza, Jhon Albert (2024)
The objective of the study was to determine differences in factors related to the level of knowledge of biosecurity measures against Covid 19 in personnel of I-4 San Juan and Bellavista Nanay health facilities. The type of research was quantitative comparative. The design was experimental cross-sectional. The sample was composed of 190 workers of both sexes, selected using a stratified sampling method, using simple random sampling (IPRESS) within each stratum. The data were collected through a survey to collect information on the level of knowledge about Covid 19. The results show that gender predominates: 81.1% female and 18.9% male. In terms of educational level, 50% have a higher education level and 45.8% have a higher education level. 49.5% were appointed and 50.5% were employees. Among IPRESS San Juan employees, 67.4% have good knowledge and 32.6% have average knowledge. Among IPRESS Bellavista Nanay employees, 77.6% have good knowledge, 15.3% have average knowledge and only 7.1% have bad knowledge. The average knowledge score of IPRESS San Juan employees was 16.39 ± 2,112 and that of IPRESS Bellavista Nanay was 16.68 ± 3,078. There were no statistically significant differences in knowledge levels by gender, age or employment status. Statistically significant differences were found in the level of knowledge according to marital status, educational level and occupational group. It was concluded that there are significant differences in knowledge about Covid19 and the factors (marital status, level of education and occupational group) in personnel of I-4 San Juan and Bellavista Nanay health facilities.